Characteristics and Classification of Innovation and Innovation Process - Danylenko, Yu.A. (Science and Innovation, 2024)
Introduction. In the past several years, innovations have become a synonym for rapid technological progress. Using cutting-edge technologies and up-to-date models for the innovation process allows corporations to be one step ahead of their competitors. Problem statement. The research of new ways for the emergence of innovations requires studying the historiography of innovation and tracking changes in the stages of innovative process development. This kind of study stimulates the appearance of modern innovative models that, in turn, can create the conditions for developing the necessary skills to introduce innovations in any context. Purpose. To examine the existing classification of innovations and models in the innovation process, to systematize and to develop author’s own classification of researched objects. Materials and methods. Logic method, comparative analysis, system approach method, and analogy method have been used for this research. Ukrainian and foreign scholarly research publications on this topic have been used as references. Results. A historiographic research of the concepts of "innovation" and "innovation process" has been carried out. Special attention is focused on the study of "open innovation". This research has enabled to retrace changes in the concept of "innovation" over time, to classify the existing types of innovations by different features and to distinguish them by categories. Along with that, the dynamics of the innovation process and the models have been scrutinized; the development stages with the respective attributes and disadvantages have been shown. Conclusions. Nowadays, there are numerous innovation types and they continue to appear constantly, though no unified classification of innovations is in place. The classifications made by Ukrainian and foreign researchers differ by the number of attributes. Moreover, at the level of individual corporation, there is no uniform action plan how to become innovative and to survive in current market economy. The top managers choose independently their innovative way taking into consideration the opportunities and challenges of the market.